PERANAN RUMAH SINGGAH AL MAUN DALAM MEMBERIKAN PENDAMPINGAN ANAK TERLANTAR DI KOTA BENGKULU - Hendi Sastra Putra (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2020)
Abstract: The most disadvantaged child is a child chosen 5-18 years due to a certain cause (due to several groups: poverty, one of the parents / guardian who is sick, one / both parents / guardian), the family is not harmonious, there is no caregiver) so it cannot fulfill basic needs physically, spiritually, or socially. In the city of Bengkulu at the present time every meeting involving children is scheduled between 5-18 years and the children are busking and asking for mercy by two-wheeled or four-wheeled motorists. Pay attention to the attention of the Bengkulu city government in handling and providing assistance to the outermost child so that in this case the bBengkulu provincial government has overcome the 1945 Constitution. Hoping the government has responsibility for the care and guidance of abandoned children. How is the concept of al-maul shelter in providing assistance to neglected children in the city of Bengkulu. to find out the role of open houses in providing assistance for abandoned children in the city of Bengkulu. Empirical Law Research is a legal research method that uses empirical facts derived from human behavior, both verbal policies obtained from interviews and research conducted through direct search. Primary data is data obtained directly from the field based on respondents and informants. Secondary data is obtained from literature books, regulations, internet browsing, and other documents. Work program stopover al maun is, access to fulfillment of children's identity, access to basic education and character of children, access to health training, skills training, development of children's interests and talents, increasing family capacity, building networks with various related parties. Keywords: Neglected Children; Al Maun Shelter; Work program;